Study of the Detection of Enteric Viruses and Bacteria in Spring-water and Groundwater in Busan (`10~`11) - Choi, Seoung-Hwa; Jeong, Jae-Eun; Yun, Na-Na; Kim, Nam-Ho; Park, Yon-Koung; Jung, Eun-Young (Journal of bacteriology and virology, 2013)
We analyzed the occurrence of enteric viruses and bacteria at 22 places of drinkable groundwater (civil defense emergency water-supply facility), 8 places of the groundwater used for drinking water in group food services, and 10places of spring-water. When the 40 concentrated samples were analyzed using nested RT-PCR and real-time RT PCR methods, norvirus and other enteric viruses were not detected in all samples tested. The detection percentages for total coliforms, Escherichia coli, Yersinia enterocolitica of fecal indicator were 57.5%, 22.5% and 7.5%, respectively. Colipages were not detected. These results suggest that high levels of fecal indicator bacteria in groundwater and spring-water are not directly related to occurrence of enteric viruses.